2017
DOI: 10.1177/0363546517724423
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Chondrotoxicity of Nonsteroidal Anti-inflammatory Drugs and Opioid Medications

Abstract: In vitro exposure of chondrocytes to single-dose equivalent concentrations of either ketorolac or meperidine demonstrated significant chondrotoxicity, while exposure to morphine or fentanyl did not lead to increased cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
0
17
1
Order By: Relevance
“…Ketorolac increased inflammation and cartilage degradation in an experimental assay in rats, 29 and chondrocyte cell death in vitro. 30 Our observations (in vitro and in vivo) did not support COX-independent anti-inflammatory local effects of ketorolac on synovial cells, and probably local infiltration is of limited value.…”
Section: Discussioncontrasting
confidence: 76%
“…Ketorolac increased inflammation and cartilage degradation in an experimental assay in rats, 29 and chondrocyte cell death in vitro. 30 Our observations (in vitro and in vivo) did not support COX-independent anti-inflammatory local effects of ketorolac on synovial cells, and probably local infiltration is of limited value.…”
Section: Discussioncontrasting
confidence: 76%
“…Moreover, a higher mortality rate among KOA patients receiving tramadol for pain control has been reported [ 12 14 ]. In addition to known systemic adverse effects, chondrotoxicity of meperidine has been shown in cartilage specimens ex vivo [ 15 ]. Furthermore, a randomized trial that assessed treatment-related effects of opioids and non-steroidal anti-inflammatory drugs reported an association between the use of transdermal fentanyl and radiographic KOA progression over 12 weeks [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to known systemic adverse effects, chondrotoxicity of meperidine has been shown in cartilage specimens ex vivo [ 15 ]. Furthermore, a randomized trial that assessed treatment-related effects of opioids and non-steroidal anti-inflammatory drugs reported an association between the use of transdermal fentanyl and radiographic KOA progression over 12 weeks [ 15 , 16 ]. However, most previous studies suffer from a low external validity, adherent to in vitro designs, and the aforementioned in-patient trial used radiographs to measure outcomes, which have been shown to be inferior to magnetic resonance (MR) imaging, in particular in early stages of the degenerative disease [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…One in vitro study 42 reported that ketorolac has a dose-dependent cytotoxic effect on human chondrocytes whereas another in vitro study 43 reported increased chondrocyte viability. Furthermore, 4 in vivo studies found increased inflammation in the joint with histological examinations following NSAIDs administration.…”
Section: Resultsmentioning
confidence: 99%
“…Abrams et al . 42 investigated the effects of a single-dose ketorolac on mature healthy human chondrocytes in vitro . Chondrocytes were harvested from sixteen donors and a bioreactor was used to expose the chondrocytes to 0.3% and 0.6% ketorolac (more COX-1 selective NSAIDs).…”
Section: Resultsmentioning
confidence: 99%